Rancang Bangun Sistem Informasi Penyewaan Mobil Dengan Menggunakan Model Waterfall - Hidayati, Nur (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
An information system is a system consisting of elements in an organization created by humans to achieve a goal that is to be able to present information accurately. The use of a good information system is needed in various business fields, including in the car rental business. Car rental is one of the businesses that provide services to the wider community, where currently the development of the business is getting faster. However, many of these car rental businesses still carry out conventional data processing. So that it causes obstacles such as searching for data and making rental reports that take a long time and there are inaccuracies in the presentation of rental reports. With these obstacles, the use of the information system has not been implemented properly, so the car rental business requires development. The purpose of the development or design of information systems is to help resolve these constraints. In order to achieve this goal, an appropriate model is needed in the design of the system such as the use of the Waterfall model. The Waterfall model is very clear in its stages and the expected final result is to be able to produce a car rental program application that can solve all obstacles in the car rental information system.